Selected Reflections on Polish Collective (Employment) Labor Law - Baran, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The aim of this article is to assess the Polish collective labor (employment) law regulations thirty-five years after the introduction of trade union pluralism. This is a sufficiently long period to venture generalized conclusions about the functioning of this subdiscipline. In this paper, I will strive to present, sine ira et studio, that is, in an impartial and objective manner, the most significant dimensions of the normative functioning of collective labor relations in a market-based economy.